Logic and the scientific method. Virus and tobacco mosaic disease – what we know about infectious agenst - Lukić, Aleksandar; Arsić Arsenijević, Valentina (Sociološki pregled, 2023)
In this paper, using the example of the discovery of viruses from the history of science in the experiments of D. J. Ivanovsky, the authors investigate how scientific research functions and how the scientific conception that could be determined as the ruling paradigm is gradually transformed. Respecting logical and scientific-methodological principles, Ivanovsky’s discoveries, in the long run, led to the discovery of viruses as completely new agents and thus to the reconstruction of the paradigm of bacteria as the smallest living disease-causing agents. Thus, he contributed to what is defined as scientific growth in the philosophy of science. Through a comparative analysis, using the example of protective masks, we will show that today there is a tendency that the basic postulates of scientific work, which imply critical examination and the possibility of refutation, are no longer sufficiently respected.
Keywords: viruses; tobacco mosaic disease; infections; science; deduction